Efficacy of Immunotherapy in Patients with Metastatic Mucosal or Uveal Melanoma. (2nd December 2018) - Mignard, Claire; Deschamps Huvier, Aurélie; Gillibert, André; Duval Modeste, Anne Bénédicte; Dutriaux, Caroline; Khammari, Amir; Avril, Marie-Françoise; Kramkimel, Nora; Mortier, Laurent; Marcant, Pierre; Lesimple, Thierry; Gaudy-Marqueste, Caroline; et al.
Abstract : Background . The objective was to assess the response rate and survival of patients with metastatic mucosal melanoma (MM) and uveal melanoma (UM) treated with anti-CTLA-4 or anti-PD-1 monoclonal antibodies (mAbs). Methods . A multicenter retrospective study was performed in 25 dermatology departments in France. All patients with stage III-C to IV MM or UM who were treated with anti-CTLA-4 or anti-PD-1 mAbs between 2008 and 2016 were included and compared after adjustment for main prognostic factors with a second cohort of patients treated with chemotherapy. Tumor response was evaluated according to RECIST v. 1.1 criteria at Week 12. Results . Four-hundred-and-thirty-nine patients were included, 229 MM (151 immunotherapy, 78 chemotherapy) and 210 UM (100 immunotherapy, 110 chemotherapy). Response rates of MM patients treated with immunotherapy were 18/151 (11.9%; 95% CI:7.2%-18.2%), versus 11/78 (14.1%, 95% CI:7.3%-23.8%) in patients treated with chemotherapy (p=0.87). No tumor response was observed in UM patients treated with immunotherapy, versus 4/110 responses (3.6%, 95% CI:1.0-9.0%) in patients treated with chemotherapy (p=0.15). The adjusted overall survival (OS) of MM patients treated with immunotherapy was longer than that of patients treated with chemotherapy HR=0.62 (95% CI: 0.43-0.91), p=0.014, with an unadjusted median OS of 15.97 months [interquartile range (IQR)=6.89-27.11] and 8.82 months [IQR=5.02-14.92], respectively. The adjusted OS of UM patients treated with immunotherapy was not significantly different from that of patients treated with chemotherapy (HR=0.98, 95% CI: 0.66–1.44) p=0.92, with an unadjusted median OS of 13.38 months [IQR=6.03-29.57] and 11.02 months [IQR=6.13-23.93], respectively. Conclusion . Immunotherapy significantly improves OS for MM. The prognosis of metastatic UM remains poor.